2020
DOI: 10.2147/oajc.s257762
|View full text |Cite
|
Sign up to set email alerts
|

<p>Determinants of Postpartum IUCD Utilization Among Mothers Who Gave Birth in Gamo Zone Public Health Facilities, Southern Ethiopia: a Case-Control Study</p>

Abstract: Background: The postpartum intrauterine contraceptive device (PPIUCD) is an effective, reliable, safe and recommended contraceptive method for the postpartum women. However, only a small proportion of women who gave birth at health facilities in the world have used it. There are limited studies about determinants of PPIUCD utilization. Therefore, this study aimed to assess determinants of postpartum IUCD utilization among mothers who gave birth in Gamo zone health facilities, southern Ethiopia. Methods: A faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 16 publications
(16 reference statements)
0
12
1
Order By: Relevance
“…These 12 eligible studies were observational study (cross-section and case–control) in design and reported in English. The sample size ranged from 188 women in Amhara [ 10 ] to 536 in South Nation Nationalities People of Region (SNNPR) [ 26 ]. The prevalence of PPIUCD reported was between 3.3% [ 10 ] and 35.2% [ 27 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These 12 eligible studies were observational study (cross-section and case–control) in design and reported in English. The sample size ranged from 188 women in Amhara [ 10 ] to 536 in South Nation Nationalities People of Region (SNNPR) [ 26 ]. The prevalence of PPIUCD reported was between 3.3% [ 10 ] and 35.2% [ 27 ] (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the present review and meta-analysis, subgroup analysis was done by regions, study population, and study design indicated that there were variations in the utilisation of PPIUCD among different included regions, population and study design in Ethiopia. Accordingly, the highest in utilization of PPIUCD was observed in Addis Ababa 25.68% (95% CI: 11.07, 40.29) [ 27 , 32 34 ], 34.09% (95% CI: 32.52, 35.66) [ 32 , 35 ], and 21.63% (95% CI: 14.45, 28.81) [ 26 , 32 , 36 ] by region, study population and study design respectively. The observed differences could be due to culture, residence, educational status and religious differences across the region.…”
Section: Discussionmentioning
confidence: 99%
“…Influencing factors included in this systematic review and meta-analysis were fertility plan (Yes, no), heard about IPPIUCD (yes, no), counseled about IPPIUD (yes, no), birth interval (<3 years, >3 years), time of counseling about IPPIUCD (on ANC, on labor), discuss about IPPIUCD with their partner (yes, no), age group [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] and level of education (literate, illiterate), knowledge (good, poor).…”
Section: Methodsmentioning
confidence: 99%
“…[ 38 ] 2020 Amhara Cross-sectional Debretabor 182 3.3 (2.85, 3.75) Seid et al. [ 39 ] 2020 SNNPR Case control Gamo 510 Lidetu et al. [ 40 ] 2017 SNNPR Cross-sectional Sidama 310 21.9 (17.3, 26.5) SNNPR: Southern Nation Nationality and Peoples Region.…”
Section: Methodsmentioning
confidence: 99%
“…Countries in the developing world had 99% of these deaths. Proper family planning [FP] could reduce pregnancy and child-birth associated complications and subsequently reduced associated mortality [1] .…”
Section: Introductionmentioning
confidence: 99%